91 Mental Health Burden of Adolescents with Dysautonomia. (19th August 2020) - Galvin, Claire; De Souza, Astrid; Potts, Jim; Sneddon, Penny; Sanatani, Shubhayan; Armstrong, Kathryn
Abstract: Background: Dysautonomia of Adolescence (DAOA) results from a dysregulation of the autonomic nervous system during puberty and affects multiple organ systems in the body. Symptoms have a significant impact on quality of life (QoL) with many adolescents reporting a poorer QoL compared to other pediatric chronic illness populations. Furthermore, there is a paucity of research looking at underlying mental health conditions in patients with DAOA that might be contributing to poor QoL. Objectives: The aim of this review was to characterize the underlying mental health status of patients with DAOA followed in a tertiary care DAOA Clinic. Design/Methods: Single-centre retrospective chart review (January 2017-November 2019) of all current patients followed in a tertiary care DAOA Clinic. Mental health challenges were classified as significant symptoms reported and/or formal diagnosis of anxiety, depression, attention deficit hyperactivity disorder, obsessive compulsive disorder, eating disorders, somatization, mood disorders, suicidal ideation, and self-harm. Frequency tables were generated for all categorical variables. Results: Seventy-three patients are currently being followed in the DAOA clinic. Fifty-five of 73 (75%) had some form of mental health challenge including 11 (15%) which had a history of suicidal ideation and/or self-harm, 12 (17%) had no mental health concerns, and 6 (8%) are unknown. Of the 55 patients with a mental health challenge, 27 (49%) were diagnosed with a mental health condition prior to formal DAOA diagnosis and 10 (18%) were diagnosed after DAOA diagnosis. Eighteen (14%) reported symptoms of a mental health challenge but no confirmed mental health diagnosis. A breakdown of mental health symptoms and diagnoses are shown in Table 1. Of the 73 current patients, 41 (56%) accessed psychology services either through the DAOA Clinic or in the community, 9 (12%) have been referred to other health care services, and 8 (11%) did not access services. Psychiatric services were required by 15 patients (21%). Conclusion: Three-quarters of DAOA patients report some mental health challenges. This emphasizes the need for psychology to support patients with DAOA. It is unclear as to whether a mental health challenge exacerbates symptoms of DAOA or DAOA symptoms negatively impact their mental health.